PENGGUNAAN MARKA MOLEKULER RAPD UNTUK IDENTIFIKASI HIBRIDA F1 KELAPA SAWIT (Elaeis guineensis Jacq) - Sri Murti Tarigan (Bernas : Jurnal Penelitian Pertanian, 2016)
The research was carried out in Molecular Biology Laboratory, Oil Palm Research Institute (IOPRI) Medan. The research was carried to examine genetic relationship between parents and their hybrids and to produce markers useful for purity hybrid testing. The analysis used in the study were RAPD. RAPD band profiles were used to detect genetic similarity among parents and progenies. Dendogram and correspondency matrix analysis were calculated by NumericalTaxonomy and Multivariate System (NTSys) versi on 2.02 sofware. This research used two populations consist of 20 progenies from BO5462D x BO5463D cross (population I) and 22 progenies from BO944T x BO713P crossing (population II), planted in Bah Jambi estate. The RAPD analysis was conducted by screening the primers gave polymorphic fragment among parent and the progeny. From 28 primers tested, 14 primers produced polymorphic marker, 11 primers monomorphic and 3 primers were unable to amplified. Among 14 primers thatproduced polymorphic bands, 7 RAPD were chosen, they OPJ-04, OPO-13, OPC-19,OPD-10, OPM-19, OPR-07, dan OPD-11. These 7 primers produced 52 bands. Primer OPJ-04 produced highest polymorphism loci (12 loci) and primer OPO-13 produced less polymorphism loci (4 loci). From the 7 primers used, there was 1 primer that can be used as genetic purity marker, this is primer OPD-11 and D_11_250 locus. Cluster analysis showed that population I, was clustered into 5 groups with genetic similarity around 62%. Group A consist of 8 progenies which were closely related to female parent and group B consist of 3 progenies closely related to male parent. Population II was clustered into two group (A and B) with genetic similarity 66%. Group A were devided into 6 sub groups, where sub group A2 consist of 8 progenies were closely related to female parent. Sub group A2, A3, dan A4 were closely related to male parent. Deviation analysis showed that in population I, there were found 3 off type progenies (number 3,8, and 15) and in population II, there were 4 off type progenies (number 26, 28, 30 dan 45).